The Byzantine Culture Model of the 12th Century in Hugo Etherianus’ view - Kapriev, Georgi (Peitho. Examina Antiqua, 2014)
The question concerning the view of Hugo Etherianus (Eteriano) is placed here in a broader context of the processes that shaped and reshaped the Byzantine culture model between the 11th and the 12th century. The newly formed culture determined the cultural situation after the fall of Constantinople in 1204 and remained valid until the end of the Byzantine period. Characterizing the Byzantines relation to the West was the key component of this model. During various theological and philosophical debates between Latin and Romaic thinkers in the 12th century in Byzantium, the nearly 20-year career of Hugo Etherianus occupied a prominent position in Constantinople. Hugo was the best Latin expert on Hellenic and Byzantine philosophy and theology in the 12th century, particularly associated with the new dialecticians. His writings and letters as well as his debates with various Byzantine philosophers and theologians are an important testimony on the parting of the Byzantine and the Latin intellectual traditions during the last quarter of the 12th century.